2005
DOI: 10.1016/j.ijgo.2005.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of raloxifene, hormone therapy, and soy isoflavone on serum high-sensitive C-reactive protein in postmenopausal women

Abstract: Estradiol valerate plus dienogest, but not raloxifene and genistein, increase serum high-sensitive C-reactive protein levels. All 3 treatments, however, have an estrogen-like effect on serum lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…With the exception of one study reporting an improvement in CRP (Hall et al, 2005), a preponderance of recently published studies administering soy protein isolate or isolated isoflavones concur with the absence of effect on CRP shown in the present study (Teede et al, 2004;D'Anna et al, 2005;Hilpert et al, 2005;Yildiz et al, 2005;Hanson et al, 2006;RyanBorchers et al, 2006). Regardless of intervention length (1 month to 3 years), vehicle of administration (soy protein isolate or isoflavone tablets) or isoflavone dose (10-129 mg), significant effects on CRP were not observed in these studies.…”
Section: Discussionsupporting
confidence: 83%
“…With the exception of one study reporting an improvement in CRP (Hall et al, 2005), a preponderance of recently published studies administering soy protein isolate or isolated isoflavones concur with the absence of effect on CRP shown in the present study (Teede et al, 2004;D'Anna et al, 2005;Hilpert et al, 2005;Yildiz et al, 2005;Hanson et al, 2006;RyanBorchers et al, 2006). Regardless of intervention length (1 month to 3 years), vehicle of administration (soy protein isolate or isoflavone tablets) or isoflavone dose (10-129 mg), significant effects on CRP were not observed in these studies.…”
Section: Discussionsupporting
confidence: 83%
“…Phytoestrogen genistein does not affect serum CRP (33), while soy-isoflavone-enriched food decreases plasma CRP (51). Yildiz et al (157) reported that estradiol valerate plus dienogest, but not raloxifene and genistein, increase serum CRP levels.…”
Section: Estrogensmentioning
confidence: 99%
“…Preferential binding to ERb has also led to discussion about isoflavones being classified as selective estrogen receptor modulators rather than simply as phytoestrogens (41)(42)(43). Certainly, there is considerable clinical evidence to indicate that isoflavones do not affect many biological processes affected by estrogen therapy (43)(44)(45)(46)(47)(48)(49)(50)(51)(52).…”
Section: Introductionmentioning
confidence: 99%